Feasibility of the Northeast Passage: The role of vessel speed, route planning, and icebreaking assistance determined by sea-ice conditions for the container shipping market during 2020–2030. (May 2021) - Wang, Yangjun; Liu, Kefeng; Zhang, Ren; Qian, Longxia; Shan, Yulong
Highlights: Sea ice is the decision variable to control the feasibility of the Northeast Passage. Icebreaker is considered in shipping season calculation and speed-ice model training. Game model is applied to depict nonlinear interaction between two shipping routes. Abstract: This study aims to examine the feasibility of the Northeast Passage for container transportation during the period of 2020–2030. A novel model is developed to study the impact of sea-ice conditions on freight rate between the Northeast Passage and Suez Canal Route on a round voyage. The sea-ice concentration and thickness are treated as key factors controlling the use of icebreakers, operational speed, and route planning in the model. Freight rates, shipowner profits, and consumer demands on both routes are determined as model outputs. Three scenarios in 2020, 2025 and 2030 respectively are used to test the model.